2012
DOI: 10.5194/amt-5-2433-2012
|View full text |Cite
|
Sign up to set email alerts
|

Combined wind measurements by two different lidar instruments in the Arctic middle atmosphere

Abstract: Abstract. During a joint campaign in January 2009, the Rayleigh/Mie/Raman (RMR) lidar and the sodium lidar at the ALOMAR Observatory (69 • N, 16 • E) in Northern Norway were operated simultaneously for more than 40 h, collecting data for wind measurements in the middle atmosphere from 30 up to 110 km altitude. As both lidars share the same receiving telescopes, the upper altitude range of the RMR lidar and the lower altitude range of the sodium lidar overlap in the altitude region of ≈ 80-85 km. For this overl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 23 publications
(27 reference statements)
2
33
0
Order By: Relevance
“…Hooper et al, 2008;Lee et al, 2014) provide additional coverage over 0-20 km. Under clear-sky conditions the Rayleigh-Mie-Raman (RMR) lidar (Baumgarten, 2010;Hildebrand et al, 2012) measures winds throughout the middle atmosphere above Andenes, northern Norway but requires complex laser transmission and detection equipment and is not portable. Ground-based Doppler lidars measure tropospheric and lower stratospheric winds (Gentry et al, 2000), with possible extension up to 50 km (Souprayen et al, 1999) and sodium lidars cover the altitude range 85-100 km (Williams et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hooper et al, 2008;Lee et al, 2014) provide additional coverage over 0-20 km. Under clear-sky conditions the Rayleigh-Mie-Raman (RMR) lidar (Baumgarten, 2010;Hildebrand et al, 2012) measures winds throughout the middle atmosphere above Andenes, northern Norway but requires complex laser transmission and detection equipment and is not portable. Ground-based Doppler lidars measure tropospheric and lower stratospheric winds (Gentry et al, 2000), with possible extension up to 50 km (Souprayen et al, 1999) and sodium lidars cover the altitude range 85-100 km (Williams et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…DoRIS is part of the Rayleigh/Mie/Raman (RMR) lidar of the ALOMAR (Arctic Lidar Observatory for Middle Atmosphere Research) observatory in Northern Norway (69 • N), which actually consists of a double lidar system and allows temperatures and winds to be measured in two directions simultaneously (von Zahn et al, 2000). A first comparison of winds measured by DoRIS and by a sodium lidar, also located at ALOMAR, showed good agreement in the limited height region of overlapping measurements around 80-85 km (Hildebrand et al, 2012). ALOMAR is located very close to the Andøya Space Center (ASC), which offers the unique opportunity to compare winds from DoRIS with in situ measurements applying rocket-borne techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Validations of the method for nighttime observations have been presented by Hildebrand et al (2012) andLübken et al (2016). Measurements of temperatures and wind during day and night are presented in Baumgarten et al (2015).…”
Section: Middle Atmospheric Wind Lidarmentioning
confidence: 99%
“…In addition to the improvement of the tropospheric forecast skills of the 15 weather predictions, the higher model lids made available re-analysis data for the stratosphere and mesosphere which are widely used in the research community. However, up to now, only few comparisons between wind observations and models exist: Kishore Kumar et al (2015) analysed the correspondence of fortnightly rocket wind soundings with the MERRA reanalysis and Hildebrand et al (2012Hildebrand et al ( , 2017 showed comparisons between January nighttime lidar measurements and ECMWF operational analysis and forecast data. The present study will show for the first long-term intercomparisons between wind 20 observations and state-of-the-art models and re-analyses (ERA5, ECMWF forecasts, MERRA2, SD-WACCM) by using the 11 months quasi-continuous data set recorded by the microwave radiometer WIRA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation